PENGARUH RASIO KEUANGAN, KEPEMILIKAN, KEBIJAKAN DIVIDEN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Bino Sulaksono; Irvine Sandra (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to obtain empirical evidence about the effect of profitability, institutional ownership, managerial ownership, dividend policy, firm size, total asset turnover and debt to equity ratio as independent variables to firm value as dependent variable. The population in this research is all non-financial companies that listed in Indonesia Stock Exchange (BEI) from 2018 to 2020. The sample used for this research consist of 63 listed non-financial companies. The selection of these sample used the purposive sampling method with total 186 research data and the data analysis method in this research is used multiple regression analysis. The result in this research indicated that profitability dan dividend policy had effect to firm value. While, institutional ownership, managerial ownership, firm size, total asset turnover dan debt to equity ratio had no effect to firm value.